A Study on Swirling Jets Flow Controlled by Two Tandem Bodies - Le, M.D. (MDPI, 2022)
This study presents the effects of using two centerbodies arranged in tandem on the flow and velocity properties of swirling jets. The centerbodies are installed concentrically downstream of the jets to modify the wake. Smoke flow visualization was employed to illustrate the flow behaviors, while the particle image velocimetry technique was utilized to investigate the velocity fields, turbulent properties, vorticities, and Lagrangian time and length scales. The toroidal recirculation and vortex shedding are found near the field using one centerbody. The recirculation zone is evolved from the edge of the centerbody, while the vortex shedding is formed by the interaction between the central and the annular jets. Since two centerbodies are installed, two four-way saddles are located near the rim of the upstream centerbody to associate two pairs of vortices. A large momentum of the annular jet dominates the flow field; therefore, the central jet forms dual-rotating vortices at downstream centerbody. The turbulent intensity and vorticity along the central axis in the case of two centerbodies are extremely lower than those in the case of one centerbody. Large turbulent intensity and vorticity are located around the shear layers of jets. This promotes a better mixing efficiency of the swirling jets. Â© 2022 by the authors. Licensee MDPI, Basel, Switzerland.